Utility of the participation and environment measure for children and youth (PEM-CY) for programmatic assessment and intervention planning: a mixed methods study - Cliff, Anna Beth, author; Khetani, Mary, advisor; Schelly, Catherine, committee member; Daunhauer, Lisa, committee member (Colorado State University. Libraries, 2013)
The purpose of this mixed methods sequential explanatory study was to examine the utility of the Participation and Environment Measure for Children and Youth (PEM-CY) for use by a community service agency, Adaptive Recreation Opportunities (ARO), for programmatic assessment and service planning to promote children's community participation. The study used two distinct, interactive phases, which included collection and analysis of quantitative data (Phase 1) and sequential collection and analysis of qualitative data (Phase 2) to determine if qualitative results could be used to further explain results from the quantitative phase. The first phase of the study (quan) included gathering PEM-CY data from 23 families who were receiving services from ARO to better understand patterns in children's community participation and environmental supports and barriers to participation in community activities. Results from Phase 1 were summarized into a report and used during Phase 2 (QUAL) to gather the perspectives of 7 ARO staff via semi-structured interviews. Phase two findings suggest that ARO staff perceived the PEM-CY to provide for a more comprehensive and detailed initial assessment process to identify individual and program-level needs. Providers were also able to delineate a core decisional process for leveraging PEM-CY results to develop an intervention plan with families. Future validation with parents and considerations for enabling collaborative and feasible uptake of the decisional process by parents and providers is discussed.
Keywords: participation; environment; mixed methods; intervention; assessment; children